Coiled Fiber‐Shaped Stretchable Thermal Sensors for Wearable Electronics. Issue 8 (7th September 2016) - He, Yonglin; Gui, Qinyuan; Liao, Shenglong; Jia, Hanyu; Wang, Yapei
Abstract : A highly stretchable fiber‐shaped sensor is prepared by coating polypyrrole on commonly used threads in a simple and scalable production. Reliable and stable sensing performance is achieved without the interference by tensile or bending strain. The sensor is washable and also convenient to be integrated into textiles, affording great opportunities for generally wearable electronics.